PENGARUH SUBSTITUSI TEPUNG BERAS DENGAN UBI JALAR UNGU TERHADAP KARAKTERISTIK “KLEPON” YANG DIHASILKAN - Sari, Debora Febrina; Sugitha, I Made; Wiadnyani, AAI Sri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 1 No 1 (2012): Jurnal ITEPA)
The aim of this research was to determine the effect of the substitution between rice flour with purple sweet potato to characteristics of “klepon” and to determine the best comparison to produce the best characteristics of “klepon”. The design of research was Randomized Block Design. Ratio of rice flour and purple sweet potato were : 100% : 0%, 90% : 10%, 80%: 20%, 70% : 30%, 60% : 40%, 50% : 50%, respectively. The treatments were replicated three times. Data were analyzed with ANOVA and if the was treatment effect on the observed variables, further analyzed by Duncan’s test. The best characteristics of “klepon” was indicated by application of ratio of rice flour 60% : purple sweet potato 40%. The following criteria water content 24,25 (% wb); ash 0,56 (% wb); protein 2,48 (% wb); fat 1,34 (% wb); carbohydrate 71,37 (% wb); and anthocyanin 0,08%, while the sensory evaluation criteria normal color, normal texture, normal aroma, taste rather liked, dan the overall acceptance criteria rather liked
Keywords: “klepon”, rice flour, purple sweet potato